2016
DOI: 10.1002/2015jd024102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a lake system in a megacity: The impact of urban expansion on seasonal meteorology in Mexico City

Abstract: The Mexico City Metropolitan Area (MCMA) has undergone significant urban expansion in a closed basin that once supported a large lacustrine system. While urbanization has been mentioned as a factor in observed meteorological trends, a systematic study of the effects of land use-land cover change (LULCC) on seasonal meteorology is lacking. In this study, we utilize the Weather Research and Forecasting (WRF) system to determine the spatiotemporal changes in near-surface air temperature, precipitation, and bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…2). For example, 600 years of urbanization has led to substantial increases in rainfall over large portions of Mexico City (8). This alone has likely exacerbated overall flood risk in the city during the rainy season.…”
Section: Case Study: Water Managementmentioning
confidence: 99%
“…2). For example, 600 years of urbanization has led to substantial increases in rainfall over large portions of Mexico City (8). This alone has likely exacerbated overall flood risk in the city during the rainy season.…”
Section: Case Study: Water Managementmentioning
confidence: 99%
“…Note that the effects of the urbanization on local climate vary with the pre‐settlement land cover type. For example, Benson‐Lira et al () found that the loss of lake cover due to urbanization in Mexico city led to daytime warming of >4 °C and night warming of ∼1 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Note that the effects of the urbanization on local climate vary with the pre-settlement land cover type. For example, Benson-Lira et al (2016) found that the loss of lake cover due to urbanization in Mexico 267 city led to daytime warming of >4 ∘ C and night warming of ∼1 ∘ C. In winter, a cooling effect due to UCE is simulated during night and day. This cooling is due to the reduction of Rnet (Figure 5(b)) and a greater portion of Rnet being allocated to heat storage, which offsets the reduction in LH (Figures 5(f) and (d)).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Weather Research and Forecasting (WRF) model (Skamarock et al, ) coupled with an urban canopy model (UCM; Kusaka et al, ) is widely used as a community tool for studying urban climatic and environmental issues (Chen et al, ). However, previous WRF/UCM simulations usually used the default (e.g., Chen et al, ; Wang et al, ) or spatially uniform AH profiles in the UCM (e.g., Benson‐Lira et al, ; Grossman‐Clarke et al, ), or even ignored the AH effect (e.g., Zhang, Gao, et al, ; Zhou & Shepherd, ; Zhang et al, ; Wang et al, ). Using the WRF/UCM model and simple setting of AH values, previous studies suggested that the contribution of AH emission to the UHI under hot weather conditions was about 22%–30% in Hangzhou and Nanjing (Chen et al, ; Chen, Zhang, & Wang, ), which are respectively the provincial capitals of Zhejiang and Jiangsu in YRD.…”
Section: Introductionmentioning
confidence: 99%